Stage lighting design - Fraser, Neil, 1958- (Crowood theatre companions., 2018)
Stage Lighting Design is a comprehensive introduction to technical theatre, tracing the evolution of lighting design from ancient drama to contemporary performance. Neil Fraser covers everything that today's designers will need to know, from the simple nuts and bolts of equipment, through to the complexity of a full lighting rig, including all aspects of the stage electrician and lighter designer's roles. This revised second edition includes new material on historical development, intelligent control systems and the latest advances in LED fixtures and luminaires. Each chapter includes key exercises, now totalling 100, that enable the reader to practise their skills on a wide variety of lighting challenges. The work of current designers is showcased and analysed, with examples from complete and detailed lighting designs.Includes: Choosing and using equipment; Applying colour; Techniques for focusing; Lighting in the round and other stage layouts; Creating mood and atmosphere; Lighting effects and LED source fixtures; Planning, testing and executing a lighting design.Superbly llustrated with over 150 colour, black & white photographs and line artworks.- Amazon.com